Hukum Keluarga Islam di Somalia - Andrio Pratama; Ikrima Imroatul A.; Sindi Nurlita A.R.; Nur Ratna Sari; Mochammad Agus Rachmatulloh (Al-Adillah: Jurnal Hukum Islam, 2022)
This article describes the development of Islamic family law in Somalia, ranging from marriage, divorce, guardianship, polygamy, wills and inheritance. In the practice of life that is in line with the times, place, time and conditions of the development and renewal of Islamic family law, it is always needed, especially after independence from the invaders. Whereas Islamic family law itself has actually been regulated in Islamic law. The formulation of the problem is: How is the development and typology of Islamic family law reform in Somalia. Using a qualitative approach with the document method and focus group discussion. The result is that the renewal of Islamic family law in 1975, called the Family Code of Somalia, contained a slight deviation from existing Islamic law and the school of thought adopted by the State, in which the issue of inheritance distribution between men and women is the same. The typology of renewal uses a progressive type of school unification and extradoctrinal reform.